Steam treatment of Pinus radiata D. Don prior to its high-temperature drying - Margadant, R. F.(Ronnie Frans) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. (Wood Science)) -- University of Stellenbosch, 1983.